The Effect of Influencer Marketing and Price on Generation Z’s Purchase Intention toward Trendy Food in Bangkinang City - Sispurwanto, Yedi; Yetti, Dzulhijjah; Kurnia, Dedi; Rukhshah, Muhammad; Pribadi, Antoni (Journal of Engineering Science and Technology Management, 2025)
This study aims to analyze the effect of influencer marketing and price on the purchase intention of trendy food among Generation Z in Bangkinang City. The rapid growth of social media has significantly influenced consumer behavior, particularly among Generation Z, who are known for their high level of digital engagement and openness to new trends. This research employs a quantitative approach using a survey method with a structured questionnaire distributed to respondents aged 17–26 years. A total of 385 valid responses were obtained through purposive sampling, assuming an infinite population. The data were analyzed using multiple linear regression to determine the significance and magnitude of the relationships between variables. The results indicate that influencer marketing has a positive and significant effect on purchase intention, suggesting that endorsements and promotions by social media personalities can effectively stimulate consumer interest. Price also shows a significant influence, indicating that affordability and perceived value remain important considerations for Generation Z consumers. These findings provide practical implications for culinary business owners and marketers in designing promotional strategies that combine influencer engagement with competitive pricing to maximize purchase intention.